El industrialismo de la naturaleza (naturaleza artificializada). Turismo industrializado - Lara González, José David (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The letter provides a short review of tourism in general and ecotourism in particular. It looks at the human need for recreation time and the relationship it has with tourism. It attempts an analysis of the phenomenon of industrialization of life and it reviews the process of industrialization that has taken place in tourism activities briefly mentioning the cultural activities in relation to tourism. It outlines the process of to artificialize the nature. It explores the distance between tourism and industrialization of nature tourism.